ChemInform Abstract: Alkoxy Base‐Mediated Transition‐Metal‐Free Cross‐Coupling Reactions of Benzene with Aryl Halides. Issue 14 (April 2015) - Liu, Wei; Xu, Lige; Bi, Yanlan
Abstract: The radical coupling of unsubstituted benzene (II) with aryl iodides (I) promoted by mixed alkoxy bases affords biaryls in moderate to good yields.